Entre ávaros e turcos: o estereótipo cita nômade na história de Menandro Protetor (século VI) - Oliveira, Rodrigo dos Santos (2021)
The Mongolian plateau, in the heart of Mongolia, served as a stage for the emergence of diverse ethnic groups and nomadic empires throughout History. However, in the sixth century, a new ethnic and linguistic entity, unknown since then, emerged in this space: the Turkic Khaganate. Led by Bumin Qaghan, in 551, the Turks managed to overthrown Yujiulu Anagui, khagan of the Rouran Khaganate, and establish their own nomadic empire, which during its peek moment in the second half of the 6th century, stretched from the north of the Caucasus in the West, to the north of Korea in the East. The rise of this new nomadic entity, however, set in motion a series of nomadic tribes such as the Avars, who between 557 and 558 settled in the Caucasus Region, where they came into contact with the Eastern Roman Empire, and in 568 settled in Pannonia, forming the Avar Khaganate. It was Menander Protektor, a sixth-century Roman historian, who narrated in his fragmentary History the establishment of the Avar Khaganate in Pannonia and one of the first diplomatic contacts between Constantinople and the Turkic khagan of Eurasia. Therefore, this research aims to analyze the representations of Menander Protektor about Avars and Turks. For this analysis, we understand that Greco-Roman literature, based on the works of Herodotus and Hippocrates, built a stereotype about nomadic groups that served as basis for future representations, specially by authors of Late Antiquity. As a theoretical approach, concepts such as stereotype, fictive ethnicity and representation will be operationalized from a post-Colonial methodological approach, in which it is understood that Greco-Roman sources structure discourses and narratives that reinforce political and ideological positions, often appropriated by the contemporary academy in order to further strengthen center-periphery relationships for modern European and Asian territories. The main documentation used for the development of this MA thesis is the History of Menander Protektor, a fragmentary work whose excerpts survived through the Suda and the Constantinian Excerpts, and were compiled and translated into English by Roger Charles Blockley (1985).